Destinasi Berkembang Menuju Klaster Maju: Kecenderungan Kunjungan Wisatawan di Klaster Danau Paisu Pok–Pantai Poganda - Basri, Iwan Setiawan; Abdurrahman, Hadi; Arifin , Rosmiaty; Mulyati , Sri; Salenda, H. (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2026)
Village- and community based tourism has increasingly been promoted as a strategy to ensure a more equitable distribution of development benefits, particularly in archipelagic regions such as Banggai Kepulauan Regency, Indonesia. This study examines tourist visitation trends in the Danau Paisu Pok Pantai Poganda Cluster during the 2022–2024 period, determines its position within the regency’s priority destination system using the Tourism Area Life Cycle (TALC) framework, and analyzes management implications from a community-based tourism (CBT) perspective, including the strengthening of regional tourism data systems, through a descriptive exploratory approach based on secondary data. The findings reveal a rapid increase in tourist arrivals, from 20,555 visitors in 2022 to 49,696 in 2023, reaching 51,669 visits by September 2024. This growth places the cluster in the growth phase of the TALC model and indicates a functional transition from an emerging destination toward an advanced tourism cluster, characterized by a visitation surge exceeding 140%, consistent official promotion, strengthened policy support, and a contribution of approximately 47.39% to total tourist arrivals in Banggai Kepulauan Regency in 2024. Institutional strengthening at the village level particularly the designation of Luk Panenteng Village as a developing tourism destination along with community empowerment through CBT, emerges as a key factor supporting the sustainable management of the tourism cluster.